Fine Needle Aspiration Cytology for the Diagnosis of Thyroid Nodules and its Correlation with Histological Diagnosis - Faran Khan (Journal of Rawalpindi Medical College, 2014)
Background: To evaluate the role of fine needle aspiration cytology (FNAc) as a diagnostic tool in investigation of thyroid swelling and to correlate cytological findings with histopathology. Methods: In this descriptive study, ninety patients of all age groups and both sexes who underwent FNAc, for thyroid nodules, were included. Out of 90 patients, histopathological diagnosis was available for 60 patients. FNAC slides were stained with Wright and Papanicolaou (PAP) stains and histopathology slides were stained with Hematoxylin and Eosin . Pre-operative FNAc results were compared with final histological diagnosis in 60 patients. The sensitivity, specificity, accuracy, false positive rate (FPR) and false negative rate (FNR) of FNAC for detection of malignant lesions was calculated. Results: Majority (80%) were females. FNAc results revealed 85.55% as non neoplastic.The commonest lesions in thyroid gland was goiter. Among the malignant neoplasms, the commonest lesion was papillary carcinoma. Anaplastic carcinoma was detected in one case.Out of 60 patients,with available histopathological diagnosis, 21 were labelled as neoplastic on FNAC. On histopathological examination, 3 out of 21 were labelled as non-neoplastic and the remaining 18 were diagnosed to be neoplastic. On FNAc 39 out of 60 patients were labelled as non-neoplastic.On histopathological examination, 3 out of 39 were labeled as neoplastic and the remaining 36 were diagnosed to be non neoplastic.The accuracy of histodiagnosis was 90% with a sensitivity of 85.7%, specificity of 92.3%, false negative rate of 14.28% and false positive rate of 7.69% .Significant agreement was observed between FNAC and histopathology results as indicated by kappa (0.69) and p value (0.001). Conclusion: FNAc of thyroid lesions is simple, easy to perform, cost effective and easily repeated procedure. It is recommended as first line method for investigating the nature of lesion.